2022
DOI: 10.1002/ana.26302
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson Disease and Subthalamic Nucleus Deep Brain Stimulation: Cognitive Effects in GBA Mutation Carriers

Abstract: Objective This study was undertaken to compare the rate of change in cognition between glucocerebrosidase (GBA) mutation carriers and noncarriers with and without subthalamic nucleus deep brain stimulation (STN‐DBS) in Parkinson disease. Methods Clinical and genetic data from 12 datasets were examined. Global cognition was assessed using the Mattis Dementia Rating Scale (MDRS). Subjects were examined for mutations in GBA and categorized as GBA carriers with or without DBS (GBA+DBS+, GBA+DBS‐), and noncarriers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 54 publications
(69 reference statements)
5
56
0
Order By: Relevance
“…Additionally, a recent study found that the rate of cognitive decline for GBA mutation carriers after bilateral subthalamic nucleus deep brain stimulation (STN-DBS) is higher than that of carriers of PRKN and LRRK2 mutations and those without identified disease-associated pathogenic variants [ 136 ] ( Figure 1 A). These findings were further corroborated by a new study which suggests that STN-DBS is associated with a greater rate of cognitive decline in GBA mutation carriers [ 137 ]. A recommendation that arose from this study is that PD patients should be screened for GBA pathogenic variants prior to DBS surgery, and that carriers of such variants should be counseled on the greater risk of cognitive decline [ 137 ].…”
Section: Genetic Testing In Parkinson’s Diseasesupporting
confidence: 52%
See 1 more Smart Citation
“…Additionally, a recent study found that the rate of cognitive decline for GBA mutation carriers after bilateral subthalamic nucleus deep brain stimulation (STN-DBS) is higher than that of carriers of PRKN and LRRK2 mutations and those without identified disease-associated pathogenic variants [ 136 ] ( Figure 1 A). These findings were further corroborated by a new study which suggests that STN-DBS is associated with a greater rate of cognitive decline in GBA mutation carriers [ 137 ]. A recommendation that arose from this study is that PD patients should be screened for GBA pathogenic variants prior to DBS surgery, and that carriers of such variants should be counseled on the greater risk of cognitive decline [ 137 ].…”
Section: Genetic Testing In Parkinson’s Diseasesupporting
confidence: 52%
“…These findings were further corroborated by a new study which suggests that STN-DBS is associated with a greater rate of cognitive decline in GBA mutation carriers [ 137 ]. A recommendation that arose from this study is that PD patients should be screened for GBA pathogenic variants prior to DBS surgery, and that carriers of such variants should be counseled on the greater risk of cognitive decline [ 137 ].…”
Section: Genetic Testing In Parkinson’s Diseasesupporting
confidence: 52%
“…However, post-operative cognitive impairment was found to be more common and severe in this group of patients (Lythe et al, 2017;Artusi et al, 2019;Mangone et al, 2020). Pal et al (2022) revealed that the combined effects of GBA mutation and STN DBS may increase the risk of cognitive decline (Pal et al, 2022). Also, non-motor symptoms (with cardiovascular symptoms as an exception) were found to be more prevalent and severe after surgery (Lythe et al, 2017).…”
Section: Other Genes That Modify Parkinson's Disease Risks or Outcome...mentioning
confidence: 75%
“…Besides, the quality of life worsened significantly in GBA mutation carriers after receiving DBS surgery, with greatest deterioration in domains such as mobility, activities of daily living, cognition, and communication (Lythe et al, 2017). Furthermore, it appeared that the severity of the type of GBA mutation was not linked to a difference in the rate of cognitive decline after operation (Pal et al, 2022).…”
Section: Other Genes That Modify Parkinson's Disease Risks or Outcome...mentioning
confidence: 99%
“…In contrast, glucocerobrosidase ( GBA ) gene variants have been associated to poorer DBS outcomes in terms of cognitive decline and non‐motor symptom burden, but not response of motor symptoms to DBS 85,86 . According to a recent multicenter observational study, cognition in STN‐DBS treated PD patients with GBA mutations deteriorates faster compared with GBA patients without DBS, suggesting that patients should be screened for GBA variants as part of the pre‐surgical work‐up and counseled accordingly 87 . Beyond this latter study, however, there are no studies assessing patients with specific PD subtypes or genetic mutations treated with DBS and comparing their outcome to the patient groups with the same phenotype or genotype that are not treated by DBS.…”
Section: Discussionmentioning
confidence: 99%